2020
DOI: 10.3390/ani10091669
|View full text |Cite
|
Sign up to set email alerts
|

On the Behavioural Biology of the Mainland Serow: A Comparative Study

Abstract: Comparative behavioural studies help reconstruct the phylogeny of closely related species. In that respect, the serows Capricornis spp. occupy an important position as they have been assumed to be the closest forms to the ancestors of Caprinae. In spite of that, information on the behavioural repertoire of the mainland serow Capricornis sumatraensis is exceedingly poor. In this paper, we report data on the activity rhythms and social behaviour of rutting mainland serows in captivity (Central Thailand, January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Notably, in contrast to the increased or stable mitochondrial genetic diversity indicated in our BSP analysis, recent studies suggest that both environmental changes and human activities have led to a decline in individual number in populations of C. sumatraensis [ 46 , 47 , 48 ]. We can infer that the decrease in individual numbers in its populations either has not affected its mitochondrial genetic diversity, or that there is a temporal latency to show its effect on genetic components.…”
Section: Discussioncontrasting
confidence: 78%
“…Notably, in contrast to the increased or stable mitochondrial genetic diversity indicated in our BSP analysis, recent studies suggest that both environmental changes and human activities have led to a decline in individual number in populations of C. sumatraensis [ 46 , 47 , 48 ]. We can infer that the decrease in individual numbers in its populations either has not affected its mitochondrial genetic diversity, or that there is a temporal latency to show its effect on genetic components.…”
Section: Discussioncontrasting
confidence: 78%
“…Indeed, site guarding is found in a limited number of species for which mating tactics are known. Geist (1974b) noted that, because of poor and discontinuous food supply, “we cannot expect northern ungulates to be territorial if they rut in fall and early winter”; accordingly, this form of mate acquisition is found in species that restrict their ranges to areas with a relatively constant food supply (Schaller 1977), such as the forest‐dwelling serow (Lovari & Locati 1994, Kishimoto 2003). Yet, relatively great and continuous plant diversity and productivity may not be a necessary condition for territoriality, as long as some predictability in spatio‐temporal resource availability occurs: for example, although Geist (1974b) suggested that chamois territoriality may be an artefact of high population density, it is likely to represent an example of seasonal resource‐based territoriality owing to predictable snow‐dependent movements of females in search of food (von Hardenberg et al 2000, Corlatti et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The competition of natural resources between two extant caprine species might have led to the decreasing populations of a smaller-sized goral N. griseus. In contrast, studies on temporal activity patterns observed in extant caprine communities have revealed that gorals are likely to be active at the beginning of daytime from dawn to late morning, while serows are energetic after late afternoon to night (Bhattacharya et al, 2012;Lovari et al, 2020). It is presumable that although the dental microwear textures suggest small differences in dietary preferences between Capricornis (soft foliage) and Naemorhedus (harder food object), niche partitioning might have occurred in other different ways.…”
Section: Niche Partitioning Between Capricornis and Naemorhedusmentioning
confidence: 98%